Modal Psikologis Positif, Kesiapan Perubahan, Dan Resistensi Perubahan Di Lembaga XYZ Padang - Wati Indah Sari; Fivi Anggraini (ProBisnis : Jurnal Manajemen, 2026)
This study examines Positive Psychological Capital's (PsyCap) effect on Resistance to Change (RTC), mediated by Readiness for Change (RFC), among 53 employees at institution XYZ Padang. Quantitative survey data were analyzed via Partial Least Squares-Structural Equation Modeling (PLS-SEM) in SmartPLS. PsyCap positively and significantly affects RFC (β=0.590, p=0.012), but shows no significant direct effect on RTC (β=-0.286, p=0.351). RFC neither significantly affects RTC (β=-0.120, p=0.753) nor mediates the PsyCap-RTC relationship (β=-0.071, p=0.754). Findings indicate PsyCap enhances change readiness, but RTC persists due to contextual factors in public organizations. Theoretical implications highlight distinct RFC-RTC constructs; practical advice urges integrated psychological-managerial change